Ответ(ы) на вопрос:
[latex](\frac{m}{m-6}- \frac{2m}{m^2-12m+36})* \frac{36-m^2}{m-8}+ \frac{12m}{m-6}= \\ =(\frac{m}{m-6}- \frac{2m}{(m-6)^2})* \frac{36-m^2}{m-8}+ \frac{12m}{m-6}=\frac{m(m-6)-2m}{(m-6)^2}* \frac{6^2-m^2}{m-8}+ \frac{12m}{m-6}= \\ =\frac{m^2-6m-2m}{(m-6)^2}* \frac{(6-m)(6+m)}{m-8}+ \frac{12m}{m-6}=\frac{m^2-8m}{(m-6)^2}* \frac{-(m-6)(6+m)}{m-8}+ \frac{12m}{m-6}= \\ =-\frac{m(m-8)}{(m-6)^2}* \frac{(m-6)(6+m)}{m-8}+ \frac{12m}{m-6}=-\frac{m(6+m)}{m-6}+ \frac{12m}{m-6} [/latex]
[latex]\frac{-(6m+m^2)+12m}{m-6}= \frac{12m-6m-m^2}{m-6}= \frac{6m-m^2}{m-6}= \frac{m(6-m)}{m-6}= \frac{-m(m-6)}{m-6}=-m [/latex]
Не нашли ответ?
Похожие вопросы